Diversidade funcional de espécies nativas utilizadas em programa de restauração ambiental - Martins, Ana Carolina Ferreira (2013)
The intensive use and disorderly of natural resources is endangering many biomes, such as Cerrado. Therefore the restoration of degraded environments is a growing activity been increasingly necessary and essential for conservation of biodiversity. The aim of this study was to evaluate the life history and adaptive capacity of species in two restoration areas compared with control individuals, i.e. individuals found in areas of Cerrado original vegetation. The studied species are part of a tree species list used by Buriti Program for environmental restoration of the riparian River Basin Uberabinha. We selected 5 species in Area 1 (Croton urucurana, Guazuma ulmifolia, Inga laurina, Inga sessilis e Tabebuia roseo-alba) and 10 species in Area 2 (Cecropia pachystachya, Croton urucurana, Guazuma ulmifolia, Inga laurina, Inga sessilis, Luhea divaricata, Myrsine umbellata, Tapirira guianensis, Tabebuia roseo-alba e Trema micrantha), being these the most representative and the best adapted in the two studied areas. We evaluated the vegetative and reproductive attributes of each species to verify the diversity of attributes in both restoration areas. Five individuals of each species have had measured diameter and checked, and 5 to 10 young fully expanded leaves were collected from each for assessment of functional leaf traits. For this, specific leaf area (SLA) was measured by the ratio leaf area (mm2)/dry weight (mg) to each sheet of the collected individuals. Were necessary scanned images of leaves (Image J) to obtain the leaf area. Already dry mass was achieved by weighing after these leaves turn for a period of at least 48 hours in an incubator at 70o C. The petiole length (PL) was estimated by the same images used for obtaining the leaf area. For date analysis we used parametric tests, ANOVA and T test, and non-parametric Kruskal Wallis and Mann-Whitney test when the assumptions were not met. The differences between means were performed using the multiple comparisons of Tukey at 5% significance. The variation coefficient each species also had been calculated for measure intraspecific variability between samples each species. There were significant differences between species of the two areas and between control for most studied species. The SLA and PL contrary to what is expected for species under intense luminosity, in these two leaf traits have lower values than species under shaded conditions, were significantly higher in Area 2 than control and Area 1. However, most species in Area 1 had AFE and PL equal or less than control and then species of Area 2. This study indicates that these species show attributes diversity necessary for ecological processes reestablishment in the two degraded areas. They are species that have ability to adjust their morphology, and probably also physiology for acclimation to environments with intense luminosity. So this species are potential for use in environmental restoration programs.